Nutritional Therapy In Ischemic Stroke Patients With Type 2 Diabetes Mellitus : A Case Report - Cipuk Muhaswitri; Diyah Eka Andayani; Taufik Mesiano (Faculty of Medicine Universitas Sebelas Maret, 2020)
Introduction: The prevalence of stroke in Indonesia increased from 8.3 per 1000 population in 2007 to 12.1 per 1000 population in 2013, based on Riset Kesehatan Dasar (RISKESDAS) 2013. Diabetes mellitus (DM) is an independent risk factor and can be modified. Hyperglycemia that occurs in the acute phase of stroke is associated with an increase in mortality and poor clinical outcome after stroke. Moreover, stroke patients are at risk of developing hypoalbuminemia due to poor intake and the presence of a chronic inflammatory process.Methods: A 66-year-old female patient with third recurrent ischemic stroke, history of uncontrolled DM, conciousness based on GCS is E3M5Vaphasia, Nasogastric tube (NGT) was inserted and there was a right facial nerve paralysis and bilateral hemiparesis . Nutritional status of patient is obese-1. During follow up period, the patient's blood glucose level ranged from 194 g/dl-345 g/dl. Nutrition therapy is given with a target of 1350 kcal (32 kcal/kg). Its composition consists of 15% protein, 25% fat and 60% carbohydrate (preferred complex carbohydrates), in the form of DM-specific formula containing inulin and monounsaturated fatty acid (MUFA). This nutritional therapy was administrated six times per day via enteral pathway, followed by the administration of micronutrients of vitamins C, B and folic acid.Result: During follow up period, the patient tolerated well with the diet. After the 14 days hospitalization, there was improvement of blood glucose level (<200 g/dL). Albumin level increases from 2.5 g/dL to 2.9 g/dl by the nutritional therapy containing protein more than 1.2 g/kg/day.Conclusion: Administering a diet with the recommended composition and formula helps control hyperglycemia and improve hypoalbuminemia in patients that can improve the patient's clinical condition.